2011
DOI: 10.1002/cphc.201100553
|View full text |Cite
|
Sign up to set email alerts
|

Bridging η2‐BO in B2(BO)3 and B3(BO)3 Clusters: Boronyl Analogs of Boranes

Abstract: Anion photoelectron spectroscopy and theoretical calculations are combined to probe the structures and chemical bonding of two boron-rich oxide clusters, B(5)O(3)(-) and B(6)O(3)(-), which are shown to be appropriately formulated as B(2)(BO)(3)(-) and B(3)(BO)(3)(-), respectively. The anion clusters are found to each possess a bridging η(2)-BO group, as well as two terminal BO groups and are analogs of B(2)H(3)(-) and B(3)H(3)(-). This finding advances the boronyl chemistry and helps establish the isolobal ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…The boronyl (BO) group with a B≡ ≡O triple bond is isovalent to the cyano (CN) group, both of which are known as monovalent σ-radicals. [46][47][48]55 A variety of boron oxide clusters were studied in the past years, demonstrating that the BO group plays a key role in their structures and bonding. The ratio of B versus O represents a new parameter to alter and tune the properties of boron oxide clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The boronyl (BO) group with a B≡ ≡O triple bond is isovalent to the cyano (CN) group, both of which are known as monovalent σ-radicals. [46][47][48]55 A variety of boron oxide clusters were studied in the past years, demonstrating that the BO group plays a key role in their structures and bonding. The ratio of B versus O represents a new parameter to alter and tune the properties of boron oxide clusters.…”
Section: Introductionmentioning
confidence: 99%
“…30 The bridging B−Au distances are much longer, consistent with a 3c-2e B−Au−B bond. Natural bond orbital (NBO) analysis confirms the highly covalent B−Au bonding, 50 20 The B−Au bonding in B 6 Au n − and B 6 Au n (n = 1−3) also closely parallels the B−(BO) bonding in boron oxide clusters [53][54][55] in terms of the terminal and bridging bonds, because Au and BO are both monovalent σ ligands analogous to H.…”
Section: B On the Vibrational Structuresmentioning
confidence: 83%
“…The sandwich structural pattern developed in this work expands the transition-metal complexes by introducing inorganic C 2v B 4 S 4 (1, [21] B(BS) 4 -, [8] and B 2 (BS) 6 . [22] These boron-rich boron sulfides proved to possess similar geometric structures with their oxide counterparts: BO, BO 2 -, B(BO) 2 -, B(BO) 3 -, [4,7,9,12] B(BO) 4 -, [8] and B 2 (BO) 6 . [22] It was also revealed that boron sulfide clusters favor the formation of the B≡S groups and there is a BS/H isolobal analogy similar to that of BO/H.…”
Section: Introductionmentioning
confidence: 99%